Does it occur or not? – A structured approach to support students in determining the spontaneity of chemical reactions - Hofer Elisabeth; Steininger Rosina (Chemistry Teacher International, 2023)
Thermodynamics is a central topic of chemistry as it holds a crucial role in understanding chemical processes. Due to its complexity, level of abstraction and amount of “mathematics”, chemical thermodynamics is one of the most challenging subjects resulting in a huge number of inappropriate conceptions. To determine whether a chemical reaction is spontaneous in a particular direction, students need to apply a huge amount of chemical knowledge when completing a complex, multi-step thinking process. In a Design-Based Research project, we developed “unmathematical” instructional material that aims at supporting students in accomplishing this demanding task. By providing a step-by-step instruction and incorporating scaffolding measures, students are guided through four successive tasks. The material was implemented in more than ten upper secondary chemistry classes and four teacher education courses and was proved to be proper for independent work, supporting students in connecting thermodynamics to basic chemical knowledge. Working on the material enables students to overcome barriers in the field of chemical thermodynamics and to successfully complete tasks in the area of thermodynamics and physical chemistry. Teachers can easily adapt the material to specific contents, levels, and teaching requirements. Further, the supportive material can be applied to offer differentiated and individualised learning paths.